Analyzing Urban Morphological Polarization through Spatial Entropy in Pangkalpinang, an Archipelagic City - I Gede Wyana Lokantara; Rafika Hilmi Nasution; . Khairunnisak (Jurnal Planologi, 2026)
Background: Secondary cities play a strategic role within national spatial systems, but often face limitations in planning capacity and environmental carrying capacity. Pangkalpinang, the capital of the Bangka Belitung Islands Province, represents an archipelagic city undergoing a rapid transition from an agrarian to a service-oriented economy. Its dispersed physical expansion over the past two decades has become increasingly challenging to manage due to the absence of a comprehensive spatial diagnosis. Methods: This study aims to diagnose spatial order and urban morphological polarization using the Shannon Entropy method, based on proximity to the city center (H’p) and road networks (H’j) across seven districts in 2000, 2010, and 2024. Results: The results indicate significant increases in entropy in Bukit Intan (H’p 0.334–0.532) and Gerunggang (H’p 0.348–0.461), suggesting decentralization along road networks. An increase in entropy in this context reflects a decline in spatial order, where land-use patterns become more dispersed and fragmented, signaling reduced planning control and a greater need for targeted growth-management interventions. Implications: The findings demonstrate that Shannon Entropy functions not only as a quantitative tool but also as an analytical approach for interpreting spatial transformation in archipelagic urban environments. Moreover, this study offers initial evidence to support policy formulation for growth control and the protection of productive land in archipelagic secondary cities. Keywords: Pangkalpinang City; Secondary Cities; Shannon Entropy; Urban Morphology; Spatial Polarization  Latar Belakang: Kota sekunder memegang peran strategis dalam sistem kewilayahan nasional, namun sering menghadapi keterbatasan kapasitas perencanaan dan daya dukung lingkungan. Pangkalpinang, ibu kota Provinsi Kepulauan Bangka Belitung, merepresentasikan kota kepulauan yang mengalami transisi cepat dari sektor agraris menuju sektor jasa. Ekspansi fisik yang tersebar selama dua dekade terakhir semakin sulit dikendalikan karena belum adanya diagnosis spasial yang komprehensif. Metode: Penelitian ini bertujuan mendiagnosis keteraturan spasial dan polarisasi morfologi kota menggunakan metode Shannon Entropy, berdasarkan kedekatan dengan pusat kota (H’p) dan jaringan jalan (H’j) pada tujuh kecamatan pada tahun 2000, 2010, dan 2024. Hasil: Hasil penelitian menunjukkan peningkatan entropy signifikan pada Bukit Intan (H’p 0,334–0,532) dan Gerunggang (H’p 0,348–0,461), yang mengindikasikan desentralisasi mengikuti struktur jaringan jalan. Peningkatan entropy dalam konteks ini mencerminkan penurunan keteraturan spasial, di mana pola penggunaan lahan menjadi lebih tersebar dan terfragmentasi, menandakan melemahnya kendali perencanaan serta meningkatnya kebutuhan akan intervensi pengendalian pertumbuhan yang lebih terarah. Implikasi: Temuan ini menunjukkan bahwa Shannon Entropy tidak hanya berfungsi sebagai alat kuantitatif, tetapi juga sebagai pendekatan analitis untuk memahami transformasi spasial di kota kepulauan. Selain itu, penelitian ini memberikan dasar awal bagi perumusan kebijakan pengendalian pertumbuhan dan perlindungan lahan produktif di kota sekunder berbasis kepulauan.Kata kunci: Kota Sekunder; Kota Pangkalpinang; Shannon Entropy, Morfologi Kota, Polarisasi Spasial